New insights into how cancer cells regulate glucose uptake by protein phosphorylation - Henriques, Andreia (2020)
Introduction: Cancer cells require increased amounts of glucose to sustain their proliferation and upregulate plasma membrane expression of glucose transporter GLUT1. In insulin responsive cells, glucose uptake requires previous phosphorylation of TBC1D4, a negative regulator of endosomal GLUT traffic. Previous work published by the host lab has discovered that protein kinase WNK1 can also phosphorylate TBC1D4 and promote the translocation of GLUT1 to the cell surface. In vitro, WNK1 also phosphorylates the homologue TBC1D1 for which a role in cancer cell glucose uptake is not known. The extent to which WNK1 and both TBC1D proteins contribute to glucose uptake in cancer cells is not understood but its characterization is required for a systems- -based understanding of glucose metabolism.